PHYTOCHEMICAL ANALYSIS AND ANTIOXIDANT ACTIVITY OF GARDENIA JASMINOIDES ELLIS AND DIOSPYROS MALABARICA KOSTEL - PRANJAL SARMAH,; DEBABRAT BAISHYA, (International Journal of Pharma and Bio Sciences, 2014)
This paper describes the investigative report on phytochemical constituents and antioxidant activity of two plants, Diospyros malabarica and Gardenia jasminoides for their potential as therapeutics. Diseases like cancer, rheumatoid arthritis, liver diseases and atherosclerosis as well as in degenerative processes associated with ageing are the consequence of various metabolic activities in our body that results in the formation of the free radicals. Antioxidant compounds play an imperative role as a health defending factor and are defined as free radical scavengers. The present study revealed higher ascorbic acid content and total phenolic content in D. malabarica than that of G. jasminoides. Free radical scavenging activity was evaluated using 1, 1-diphenyl-2-picrylhydrazyl (DPPH) free radical. The overall antioxidant activity of D. malabarica was more than that of G. jasminoides. All the methanolic extracts exhibited antioxidant activity significantly in both the plant extracts. The IC50 value of the methanolic extracts ranges from 8.68 ± 1.43 to 61.17±0.65 μg/ml. This report is thus suggestive of the potential of these two plants as therapeutic agent by virtue of their antioxidant activity.